Korporativna varnost - Dvojmoč, Miha (University of Maribor Press, 2025)
Corporate Security. The field of corporate security is becoming increasingly important in the modern business environment for the stable and sustainable operation of organizations. It is a comprehensive system of risk management, ensuring resilience and maintaining stakeholder trust. Corporate security, in the broadest sense of the word, is an activity that identifies and implements measures to manage risks in an organization. Its task is to protect the organization, its technologies, employees, technical resources and all customer data and information from internal and external threats. The entire implementation of corporate security must operate in accordance with the operation of the entire organization and its business processes.